(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess patient satisfaction during hospitalization at the Obstetrics Department of Quang Ninh Obstetrics and Pediatrics Hospital. Subjects and methods: A cross-sectional descriptive study was conducted involving 84 patients who underwent uterine fibroid surgery at the Obstetrics Department of Quang Ninh Obstetrics and Pediatrics Hospital. Results: Inpatients’ satisfaction with service accessibility was rated with a mean score ranging from 4.83 ± 0.37 to 4.89 ± 0.31. Transparency in information and medical care received a 100% satisfaction rate. Infrastructure and facilities for patients were rated between 4.89 ± 0.31 and 4.96 ± 0.18. Healthcare staff’s attitude and professional competence were highly rated, with scores from 4.89 ± 0.31 to 4.96 ± 0.18. Service delivery for patients was evaluated between 4.88 ± 0.32 and 4.92 ± 0.25. Conclusion: Inpatients at the Obstetrics Department of Quang Ninh Obstetrics and Pediatrics Hospital reported a very high level of satisfaction, reaching 100% across all evaluated categories.